Pemanfaatan Liveworksheet Sebagai Media Pembelajaran Berbasis Literasi Pada Mata Pelajaran Pendidikan Pancasila di SMK Negeri 7 Semarang - Sofi’atun, Sofi’atun; Purwosaputro, Supriyono; Moch Hajir, Said; Suneki, Sri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This article discusses the use of Liveworksheets as a Literacy-Based Learning Media in Pancasila Education Subjects at SMK N7 Semarang. The basis of this research is the lack of use of technology in Civics learning at SMK N 7 Semarang. This research aims to describe and analyze the use of Liveworksheets as a Literacy-Based Learning Media in Pancasila Education Subjects at SMK N 7 Semarang using a qualitative approach. With a research focus on the use of live worksheets as a literacy-based learning medium in Pancasila education subjects at SMK N 7 Semarang. This research uses a qualitative descriptive method which includes direct observation, in-depth interviews, and document collection and analysis as the main approach. The research results show that technology-based learning through the use of live worksheet applications allows the transformation of traditional worksheets into digital documents so that they can be accessed online and automatically correct wrong answers. The conclusion of using live worksheet media in learning Pancasila Education at SMK N 7 Semarang has a number of advantages that can increase its effectiveness, such as providing additional information, increasing learning abilities, making it easier to access material, making material more interesting, and increasing interest in learning.